Advances in nano-delivery of phytochemicals for glioblastoma treatment - Melvin Anyasi Ambele; Lorraine Tshegofatso Maebele; Thanyani Victor Mulaudzi; Tsholofelo Kungoane; Botle Precious Damane (Discover Nano)
Abstract Glioblastoma (GBM) is an aggressive brain tumor characterized by cellular and molecular diversity. This diversity presents significant challenges for treatment and leads to poor prognosis. Surgery remains the primary treatment of choice for GBMs, but it often results in tumor recurrence due to complex interactions between GBM cells and the peritumoral brain zone. Phytochemicals have shown promising anticancer activity in in-vitro studies and are being investigated as potential treatments for various cancers, including GBM. However, some phytochemicals have failed to translate their efficacy to pre-clinical studies due to limited penetration into the tumor microenvironment, leading to high toxicity. Thus, combining phytochemicals with nanotechnology has emerged as a promising alternative for treating GBM. This review explores the potential of utilizing specific nanoparticles to deliver known anticancer phytochemicals directly to tumor cells. This method has demonstrated potential in overcoming the challenges of the complex GBM microenvironment, including the tight blood–brain barrier while minimizing damage to healthy brain tissue. Therefore, employing this interdisciplinary approach holds significant promise for developing effective phyto-nanomedicines for GBM and improving patient outcomes.